Hyperthermia Differently Affects Connexin43 Expression and Gap Junction Permeability in Skeletal Myoblasts and HeLa Cells - Ieva Antanavičiūtė; Vida Mildažienė; Edgaras Stankevičius; Thomas Herdegen; Vytenis Arvydas Skeberdis (Mediators of Inflammation)
Stress kinases can be activated by hyperthermia and modify the expression level and properties of membranous and intercellular channels. We examined the role of c-Jun NH2-terminal kinase (JNK) in hyperthermia-induced changes of connexin43 (Cx43) expression and permeability of Cx43 gap junctions (GJs) in the rabbit skeletal myoblasts (SkMs) and Cx43-EGFP transfected HeLa cells. Hyperthermia (42°C for 6 h) enhanced the activity of JNK and its target, the transcription factor c-Jun, in both SkMs and HeLa cells. In SkMs, hyperthermia caused a 3.2-fold increase in the total Cx43 protein level and enhanced the efficacy of GJ intercellular communication (GJIC). In striking contrast, hyperthermia reduced the total amount of Cx43 protein, the number of Cx43 channels in GJ plaques, the density of hemichannels in the cell membranes, and the efficiency of GJIC in HeLa cells. Both in SkMs and HeLa cells, these changes could be prevented by XG-102, a JNK inhibitor. In HeLa cells, the changes in Cx43 expression and GJIC under hyperthermic conditions were accompanied by JNK-dependent disorganization of actin cytoskeleton stress fibers while in SkMs, the actin cytoskeleton remained intact. These findings provide an attractive model to identify the regulatory players within signalosomes, which determine the cell-dependent outcomes of hyperthermia.